2014
DOI: 10.1016/j.bbmt.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Upfront Consolidation Combining Yttrium-90 Ibritumomab Tiuxetan and High-Dose Therapy with Stem Cell Transplantation in Poor-Risk Patients with Diffuse Large B Cell Lymphoma

Abstract: We evaluated the safety and efficacy of standard-dose yttrium-90 (Y(90)) ibritumomab tiuxetan combined with high-dose BEAM (carmustine, etoposide, cytarabine, and melphalan) after first-line induction treatment in young patients with poor prognoses diffuse large B cell lymphoma (DLBCL) (clinicaltrials.gov: NCT00689169). Seventy-five high-risk (≥2 International Prognostic Index [IPI] factors) consecutive DLBCL patients (≤65 years old) in complete remission (CR) or partial remission (PR) after rituximab chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…There was moderate risk of bias in the domain of study participation in seven studies, because six studies did not report whether refractory/relapsed disease was histologically verified and one study reported that histological verification of relapsed disease was not performed in all cases. There was moderate risk of bias in the domain of prognostic factor measurement in seven studies, because five studies did not report which PET system (stand‐alone PET or integrated PET/CT) was used, and two studies used a stand‐alone PET system instead of an integrated PET/CT system. There was high risk of bias in the domain of outcome measurement in 10 studies , because these studies did not report whether relapse after ASCT was histologically verified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was moderate risk of bias in the domain of study participation in seven studies, because six studies did not report whether refractory/relapsed disease was histologically verified and one study reported that histological verification of relapsed disease was not performed in all cases. There was moderate risk of bias in the domain of prognostic factor measurement in seven studies, because five studies did not report which PET system (stand‐alone PET or integrated PET/CT) was used, and two studies used a stand‐alone PET system instead of an integrated PET/CT system. There was high risk of bias in the domain of outcome measurement in 10 studies , because these studies did not report whether relapse after ASCT was histologically verified.…”
Section: Resultsmentioning
confidence: 99%
“…There was moderate risk of bias in the domain of prognostic factor measurement in seven studies, because five studies did not report which PET system (stand‐alone PET or integrated PET/CT) was used, and two studies used a stand‐alone PET system instead of an integrated PET/CT system. There was high risk of bias in the domain of outcome measurement in 10 studies , because these studies did not report whether relapse after ASCT was histologically verified. There was high risk of bias in the domain of study confounding in 11 studies due to several reasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in two patients, consolidation with 90 Y-IT either as a single agent or as part of high-dose intensification therapy is feasible in PTLD similarly to NHL (19,20). Finally, earlier treatment 90 Y-IT may be beneficial as observed in NHL (21).…”
Section: Discussionmentioning
confidence: 83%
“…20, 4244 Consistently, 90 yttrium-ibritumomab tiuxetan has been found to have a favorable safety profile; it generally does not add toxicity to BEAM, although a trend toward increased mucositis has been noted. In a matched-cohort analysis of autologous transplant conditioning regimens for diffuse large cell lymphoma, radioimmunotherapy-based conditioning had a similar relapse incidence to TBI but with lower toxicity.…”
Section: Discussionmentioning
confidence: 90%